Spontaneous Gastric Perforation in Neonates: A Tertiary Pediatric Surgical Center Experience - Abdelghany EM Abdelgawad; Ahmed A Darwish; Emely Hughes; Eleri Cusick (EL-Med-Pub, 2019)
Objective: To report our experience with spontaneous neonatal gastric perforation (SNGP) in a tertiary hospital over the last 9 years. Methods: Retrospective review of neonates with SNGP treated in Bristol Royal Hospital for Children between January 2010 and December 2018 was performed. Data retrieved included demography, perinatal clinical details, operative data, and outcome. Cases with esophageal atresia, necrotizing enterocolitis or distal obstruction were excluded. Results: Of 13 cases, 4 were males and 9 females. Two neonates were full term; while 11 were preterm with median gestational age of 28 weeks. Abdominal distension and metabolic acidosis were mostly found in these patients. Patent ductus arteriosus was encountered in 53.8% of the patients. The most common site of perforation was the greater curvature (38.4%) followed by posterior wall (30.8%) of the stomach. Primary repair was performed in all cases. One neonate developed recurrent perforation in the early postoperative period. Five preterm (38.5%) neonates succumbed in our series. Conclusion: SNGP is a rare condition increasingly diagnosed in preterm neonates. Greater curvature and posterior wall of stomach are commonly involved. Despite recent advances in intensive care, the prognosis is still poor in preterm babies with multiple associated problems.